Participatory visioning in transport backcasting studies: Methodological lessons from Andalusia (Spain). (January 2017) - Soria-Lara, Julio A.; Banister, David
Abstract: The backcasting approach is being increasingly used in the field of transport to address issues of climate change. While it acknowledges that a structured involvement of stakeholders should become central in transport backcasting studies, there are very few policy relevant papers that pay special attention to stakeholder participation in the visioning phase of backcasting. This paper aims at showing the findings of a participatory visioning study as a starting point of a wider backcasting analysis for the transport sector (2050) in Andalusia (Spain). It presents a methodological approach that involves a total of 40 stakeholders and combines two participatory techniques: (i) Delphi survey; (ii) semi-structured interviews. The main outcomes show how stakeholders were engaged in the participation process through each technique. It then identifies five relevant methodological issues for a more detailed discussion: (i) the selection of participants; (ii) the means to visualise long-term futures; (iii) the visualisation of desired futures; (iv) the generation of multiple future visions; (v) the combination of multiple participatory techniques. In parallel, the study also presents the means by which the use of both participatory techniques can provide a narrative of a future vision for the transport sector in Andalusia. That vision focuses largely on lower carbon emissions, technological innovation, and urban compactness.